Prevalence and associated factors of depression among refugees in East Africa: a systematic review and meta-analysis - Abdu Hailu Shibeshi; Bizunesh Fantahun Kase; Abdulkerim Hassen Moloro; Molla Getie Mehari; Abubeker Alebachew Seid (BMC Psychiatry, 2024)
Abstract Introduction : Depression is a common and debilitating mental health issue among refugees in East Africa, who face numerous challenges. However, there is a lack of systematic reviews and meta-analyses that have explored the pooled prevalence and associated factors of depression among refugees in East Africa. This study aims to investigate the pooled prevalence of depression and its associated factors among refugees living in East Africa. Methods A systematic search was conducted across several databases, including PubMed/MEDLINE, CINAHL, ScienceDirect, African Journals of Online (AJOL), and Google Scholar. The quality of the included studies was assessed using a Joanna Briggs Institute (JBI) quality appraisal tool. Statistical analysis was carried out using STATA-17 software packages, and a meta-analysis was conducted using a random-effects model. Heterogeneity among the studies was assessed using the I2 statistic. Publication bias was evaluated using the DOI plot, Luis Furuya Kanamori (LFK) index, and Egger’s test. For associated factors of depression, effect sizes (odds ratio) with 95% confidence intervals were analyzed. Result A total of eight studies involving 6,388 participants were included in this systematic review and meta-analysis, all of which were assessed to have a low risk of bias. The pooled prevalence of depression was 50.60%, with a 95% CI (35.49%, 65.71). Regarding factors associated with depression; being female [(OR = 2.01; 95% CI (1.06, 3.82)], having poor social support [OR 5.88; 95% CI (2.53, 13.67)], and experienced eight or more traumatic events [OR = 3.31;95% CI (1.74, 6.31) were positively associated factors with depression. Conclusion The pooled prevalence of depression among refugees in East Africa was found to be significantly high. Female participants, poor social support, and experienced eight or more traumatic events were factors affecting depression among refugees in East Africa. Therefore, policymakers and health personnel in East Africa should prioritize addressing the needs of female participants, individuals with poor social support, and those who have experienced eight or more traumatic events.